Fourth Hankel determinant for subclasses of Bounded Starlike Function / Atira Azira Zakri, Nur Naqibah Ali and Nurfatin Fadhilah Zain Karimy - Zakri, Atira Azira; Ali, Nur Naqibah; Zain Karimy, Nurfatin Fadhilah (2019)
Let B denoted the class of functions f ( z) which are analytic with an open unit disc E = {z: z ϵR andlzl < l} and satisfy Re{ af'(z) + ,Bzf "(z )} > 0 for some O < α ≤ 1 and O ≤ β < 1 where f ( z) is a normalized starlike function. One of the properties of class of function B can be determined by finding fourth Hankel determinant for this class of function. In order to find fourth Hankel determinant, there are a few steps will be used. The extreme function must be first determined for the function of a certain class in order to study the properties. Next, compare the coefficients of like powers of z, z2, z3 and z4 between left hand side and right-hand side of function. Then, we obtain coefficient in terms of an and substitute the value of the coefficient in the functional.